Mathematical modelling of the stress resistance induced in Listeria monocytogenes during dynamic, mild heat treatments. (December 2019) - Garre, Alberto; González-Tejedor, Gerardo A.; Aznar, Arantxa; Fernández, Pablo S.; Egea, Jose A.
Abstract: Modelling of stress acclimation induced by thermal inactivation of Listeria monocytogenes under dynamic conditions is analyzed in this work. A mathematical model that separates the effect of the instantaneous temperature from the one of stress acclimation, was used. The model was trained using isothermal inactivation experiments, and one biphasic dynamic treatment with a heating rate of 1 °C/min and a holding phase of 60 °C. These experiments were performed in laboratory media (Tryptic Soy Broth; TSB). The model parameters estimated through these experiments ( D 55 = 12.87 ± 0.82 m i n, z = 4.58 ± 0.04 ° C, a = 0.11 ± 0.01 m i n − 1, E = 0.50 ± 0.01 ° C and c = 1.23 ± 0.03 ) were successfully used to predict the microbial inactivation for another seven inactivation profiles, with and without a holding phase. Moreover, similar experiments were performed using milk as heating media, obtaining a good agreement between the model predictions and the empirical observations. The results of this study are compatible with the hypothesis that L. monocytogenes is able to develop a physiological response during dynamic treatments that increases its thermal resistance. Also, that the model used can be used to predict microbial inactivation of this microorganism taking into consideration stress acclimation. Highlights: Heating rates affect inactivation kinetics of Listeria monocytogenes. Results are consistent with a physiological response that increases thermotolerance. A model has been applied to predict the microbial inactivation including acclimation. Experiments performed in TSB are adequate to predict inactivation in milk. Stress acclimation can be critical when designing dynamic thermal treatments.